Faktor Yang Mempengaruhi Akuntabilitas Keuangan Desa pada Pemerintah Kecamatan Loloda Utara: Factors that Influence Village Financial Accountability in the North Loloda District Government - sahrul; Meiti Dorci Pumadada (Universitas Bojonegoro, 2024)
This research aims to determine, analyze and empirically prove the factors that influence village financial accountability in the North Loloda District Government. This type of research is associative research that is causal in nature. The population in this study consisted of the Village Head, Village Secretary, Village Treasurer, BPD, Head of Finance and Community Participation in each village government in North Loloda District with a sampling technique using the sloving method so that the research sample totaled 85 respondents. The data in this research is primary data with data collection techniques using questionnaires. The data analysis model uses multiple linear regression analysis. The results of the research show that simultaneously Financial Management, Quality of Human Resources, Supervision and Community Participation have a significant effect on Village Financial Accountability in the North Loloda District Government and partially, Financial Management, Quality of Human Resources, Supervision and Community Participation have a significant effect on Village Financial Accountability in the North Loloda District Government